First report of Oxa-72-producing Acinetobacter calcoaceticus in Lebanon. (January 2016) - Al Atrouni, A.; Kempf, M.; Eveillard, M.; Rafei, R.; Hamze, M.; Joly-Guillou, M.-L.
Abstract: Emergence of carbapenem-resistant Acinetobacter spp. has been increasingly reported worldwide. We report here the first detection of an Acinetobacter calcoaceticus isolate from vegetables in Lebanon carrying the bla Oxa-72 gene. These findings show that the Lebanese environment may constitute a potential reservoir for this antibiotic resistance gene.